Ruderal flora of Vila Santo Amaro, General Câmara, Rio Grande do Sul, Brasil – Origin and geographical distribuition. - Carneiro, Andréia Maranhão (2005)
The spontaneous vascular vegetation from Santo Amaro Village, located in the Central Depression (29º56’S, 51º53’W), Rio Grande do Sul, was studied through a floristic research on streets, walkways, walls, and vacant lots within urban extension of the village. 302 species were found, where 59.93% are native, 37.09% exotic, and 2.98% had no identified origin. The obtained results were compared with other floristic researches where common species from Santo Amaro and other locations have been found.